MODELAGEM E VARIAÇÃO DO CRESCIMENTO AO LONGO DO FUSTE DE ÁRVORES FEMININAS E MASCULINAS DE Araucaria angustifolia - Rickli, Milayne Lopes (2020)
This work had as general objective to carry out studies of modeling and growth variation along the stem of female and male Araucaria angustifolia trees in native forest. It had as specific objectives, verify the growth pattern through the construction of chronologies; model its growth in relation to the diameter, the height of the chest (at 1.30 m from the ground), height and volume (DBH, h, v) for male and female trees; determine the passage time in diametric classes for male and female trees; compare different methods for defining the optimal cut diameter for A. angustifolia; and to verify the variation of the annual increase of wood along the stem of A. angustifolia, analyzing the influence of dioicia. For this, data came from 45 individuals from Araucária were used, with diameters ranging from 40 to 70 cm, which were located in a fragment of Mixed Ombrophilous Forest (FOM) located in the city of Fernandes Pinheiro, PR. These individuals were selected taking into account the condition of the straight stem; the sociological position in the upper extract; plant health classified as good and crown position. In addition, the definition of female and male individuals was taken into account. Five discs were removed from each individual, the first being removed close to the height of 0.1 m, discs 2 and 3 removed from the commercial portion of the stem, the third being removed in the position of the top of the crown, discs 4 and 5 were removed, respectively, at 33% and 66% from the beginning of the crown. The Complete stem analysis (ANATRO) was performed on these discs, where the growth rings were measured, reconstituting the entire growth of the trees. In addition, based on the diameter increase of the disc removed at the base of the trees, the DBH values for each age were estimated. With ANATRO data, three growth models in diameter with bark (DBH), total height and total volume with bark were adjusted for male and female individuals and for classes of trees with higher and lower than average growth, and using the best ChapmanRichards model, Current Annual Increment (CAI) and Mean Annual Increment (MAI) curves were constructed to assess growth and production. Still, from the adjustments of the ChapmanRichards model, the passage time was determined in diametric classes for female and male trees. Two methods were compared to define the minimum logging diameter (MLD) and determine the cut cycle for A. angustifolia, the method used by Schöngart and the method using data from ANATRO. Regarding the CAI and MAI curves, the maximum average annual increase observed for the diameter was 0.56 cm.year-1 and occurred at 56 years; for height it was 0.38 m.year-1 at 14 years and for volume 0.026 m³.year-1 at 176 years. The results obtained by the analysis of the passage time allowed us to verify that there is a tendency for the time between the classes to increase as the diameter increases, except for the smaller diameter class (0-10 cm), with male individuals taking a longer passage time between classes. In the definition of MLD, it was observed that for Schöngart's method, the MLD was 34.77 cm of DBH at 62 years old, and for the method using ANATRO, the MLD was 47.69 cm of DBH at 100 years old. Regarding the variation of the increment along the stem, the sampled trees tend to reach a cylindrical shape at the age of 90. As for dioicia, male individuals have higher values in increments up to 60 years, what can be explained by the reproduction cycle of female individuals, which causes a greater expenditure of energy and influences the growth of the tree.